Electric-Field-Assisted Organic Synthesis: A New Frontier in Reactivity Control - Chadwick, Huw; Cocking, Georgia; Westphäling, Johannes; Melen, Rebecca L.; Wirth, Thomas (SynOpen)
The application of oriented external electric fields (OEEFs) to modulate chemical reactivity-termed electric field catalysis-is emerging as a powerful strategy in synthetic chemistry. Inspired by nature's use of internal fields in enzymatic systems, this approach offers the potential to control reaction pathways, improve selectivity, and reduce energy input. While the theoretical foundations are robust, practical implementation remains challenging, particularly due to difficulties in generating stable, precisely oriented fields at the molecular scale.Recent advances, however, are addressing these obstacles. Notably, the use of multiwalled carbon nanotubes (MWCNTs), owing to their nanoscale architecture, electrical conductivity, and chemical robustness, has enabled the creation of electromicrofluidic devices capable of delivering localized electric fields with high spatial precision.Collaborative efforts, including those by the Matile group and our own, have demonstrated the viability of these platforms in catalysis. These developments mark a significant step toward the broader adoption of electric fieldassisted synthesis in organic chemistry.